Towards Understanding of Contextual Factors in Information Sharing Behaviors of Inter-Team Activities - Xiao, Lu; Buchel, Olga; Martin, Jennifer; Huang, Dongyan (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2016)
Activities involving two or more teams to share information and make collective decisions are increasingly common. However, little has been investigated about these behaviors. We have been studying two engineering teams of different national culture to understand the contextual factors that affect the teams’ interactions and information sharing behaviors. Les activités impliquant deux ou plusieurs équipes devant partager des informations et prendre des décisions ensemble sont de plus en plus communes. Cependant, Il existe peu de recherches sur ces comportements. Nous avons étudié deux équipes d'ingénierie provenant de cultures nationales différentes afin de comprendre les facteurs contextuels qui affectent les interactions entre les équipes et leurs comportements de partage d'information.